'Some strange version of Marxism' The Luria-Chomsky exchange. (July 2019) - Jones, Peter E.
Abstract : This article looks back at the intriguing exchange in the 1970s between Alexander Luria and Noam Chomsky over fundamental questions of linguistic theory and Marxist philosophy. Luria rejected the biological reductionism inherent in Chomskys linguistic theory while expressing deep admiration for Chomsky's linguistic 'science', specifically the separation of a level of linguistic form from meaningful content or language use. Chomsky, in return, impugned the philosophical assumptions ('some strange version of Marxism') from which Luria built his critique of Chomsky's nativism. This article argues that Luria accepted far too readily the scientific status of Chomsky's linguistic methodology and thereby compromised essential principles of the Vygotskian 'cultural-historical' psychology that Luria wished to defend and promote.